At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Alright, let’s solve the given equation step-by-step by completing the square.
Given equation:
[tex]\[ -3x^2 - 298 = -60x - 1 \][/tex]
First, we need to move all terms to one side of the equation to set it equal to zero:
[tex]\[ -3x^2 + 60x - 297 = 0 \][/tex]
Next, normalize the equation by dividing all terms by [tex]\(-3\)[/tex], the coefficient of [tex]\(x^2\)[/tex]:
[tex]\[ x^2 - 20x + 99 = 0 \][/tex]
To complete the square, take the coefficient of [tex]\(x\)[/tex] (which is [tex]\(-20\)[/tex]), halve it, and then square it to find the term to complete the square:
[tex]\[ \left(\frac{-20}{2}\right)^2 = 100 \][/tex]
Add and subtract this number inside the equation:
[tex]\[ x^2 - 20x + 100 - 100 + 99 = 0 \implies (x - 10)^2 = 199 - 1 \implies (x - 10)^2 = 199 \][/tex]
So the intermediate step in the form [tex]\((x + a)^2 = b\)[/tex] is
[tex]\[ (x - 10.0)^2 = 199.33333333333331 \][/tex]
Therefore, the correct intermediate step is:
[tex]\[ (x - 10.0)^2 = 199.33333333333331 \][/tex]
Given equation:
[tex]\[ -3x^2 - 298 = -60x - 1 \][/tex]
First, we need to move all terms to one side of the equation to set it equal to zero:
[tex]\[ -3x^2 + 60x - 297 = 0 \][/tex]
Next, normalize the equation by dividing all terms by [tex]\(-3\)[/tex], the coefficient of [tex]\(x^2\)[/tex]:
[tex]\[ x^2 - 20x + 99 = 0 \][/tex]
To complete the square, take the coefficient of [tex]\(x\)[/tex] (which is [tex]\(-20\)[/tex]), halve it, and then square it to find the term to complete the square:
[tex]\[ \left(\frac{-20}{2}\right)^2 = 100 \][/tex]
Add and subtract this number inside the equation:
[tex]\[ x^2 - 20x + 100 - 100 + 99 = 0 \implies (x - 10)^2 = 199 - 1 \implies (x - 10)^2 = 199 \][/tex]
So the intermediate step in the form [tex]\((x + a)^2 = b\)[/tex] is
[tex]\[ (x - 10.0)^2 = 199.33333333333331 \][/tex]
Therefore, the correct intermediate step is:
[tex]\[ (x - 10.0)^2 = 199.33333333333331 \][/tex]
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.